Korean Guidelines for Diagnosis and Management of Idiopathic Nonspecific Interstitial Pneumonia - Yong Suk Jo; Hyun-Kyung Lee; Sun Hyo Park; Joon Sung Joh; Hye Jin Jang; Jong Sun Park (Tuberculosis and Respiratory Diseases)
Idiopathic nonspecific interstitial pneumonia (iNSIP) is recognized as a distinct entity among various types of idiopathic interstitial pneumonias. It is identified histologically by the nonspecific interstitial pneumonia pattern. A diagnosis of iNSIP is feasible once secondary causes or underlying diseases are ruled out. Usually presenting with respiratory symptoms such as shortness of breath and cough, iNSIP has a subacute or chronic course. It predominantly affects females aged 50 to 60 years who are non-smokers. Key imaging findings on chest high-resolution computed tomography include bilateral reticular opacities in lower lungs, traction bronchiectasis, reduced lung volumes and, ground-glass opacities. Abnormalities are typically diffuse across both lungs with subpleural distributions. Treatment often involves systemic steroids, either alone or in combination with other immunosuppressants, although evidence supporting effectiveness of these treatments is limited. Prognosis is generally more favorable for iNSIP than for idiopathic pulmonary fibrosis, with many studies reporting a 5-year survival rate above 70%. Antifibrotic agents should be considered in a condition, termed progressive pulmonary fibrosis, where pulmonary fibrosis progressively worsens.